2023
DOI: 10.1186/s12951-023-02118-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the translational potential of PLGA nanoparticles for intra-articular rapamycin delivery in osteoarthritis therapy

Jian-Chao Ma,
Tingting Luo,
Binyang Feng
et al.

Abstract: Osteoarthritis (OA) is a prevalent joint disease that affects all the tissues within the joint and currently lacks disease-modifying treatments in clinical practice. Despite the potential of rapamycin for OA disease alleviation, its clinical application is hindered by the challenge of achieving therapeutic concentrations, which necessitates multiple injections per week. To address this issue, rapamycin was loaded into poly(lactic-co-glycolic acid) nanoparticles (RNPs), which are nontoxic, have a high encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…RNPs reduced the need for multiple injections, promoted chondrogenic cell differentiation in ATDC5 cells, and prevented oxidative stress-induced senescence in articular chondrocytes. 65 Sohn et al also showed that RAP lipid NPs induce immunomodulation of type II collagen in joints and alleviate OA by suppressing inflammation. 85
Figure 3 ( A ) Diagram illustrating the active loading of meloxicam liposomes (MLX-Ca(AC) 2Lipo) and its key benefits over passive loading methods, including efficient drug encapsulation, secure drug storage, and controlled drug release.
…”
Section: Nanotherapeutic Strategies For Oamentioning
confidence: 99%
See 1 more Smart Citation
“…RNPs reduced the need for multiple injections, promoted chondrogenic cell differentiation in ATDC5 cells, and prevented oxidative stress-induced senescence in articular chondrocytes. 65 Sohn et al also showed that RAP lipid NPs induce immunomodulation of type II collagen in joints and alleviate OA by suppressing inflammation. 85
Figure 3 ( A ) Diagram illustrating the active loading of meloxicam liposomes (MLX-Ca(AC) 2Lipo) and its key benefits over passive loading methods, including efficient drug encapsulation, secure drug storage, and controlled drug release.
…”
Section: Nanotherapeutic Strategies For Oamentioning
confidence: 99%
“…PNPs are versatile for drug delivery, as drugs can be encapsulated within nanomaterials and polymer molecules, chemically bound to polymers, or bound to the surface of nanomaterials. 65 Thus, compounds, both hydrophobic and hydrophilic in nature, together with drugs of varying molecular weights, can be delivered via them. 66 Synthetic polymer NPs offer advantages such as good biocompatibility, controlled release, and high drug-carrying capacity, but they also face challenges with degradation rate, stability, and safety.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Complex approval processes for new materials may prolong the time to clinical translation, as the safety and efficacy of NPs must undergo rigorous review. 679 , 680 Criteria for review include NP characterization and toxicity, where characterization would include size, shape, surface charge, stability, etc. In addition, unlike the singularity of preclinical research, clinical translation requires the cooperation of multiple departments, such as R&D institutions, experimental centers, regulatory agencies, and financial support.…”
Section: The Limitations/challenges Of Nanotechnology Applicationmentioning
confidence: 99%
“… 17 Stressful conditions such as inflammation or elevated ROS levels cause chondrocyte anabolism to decrease, while catabolism increases, hastening the onset of OA. 18 As translational therapeutics, multifaceted techniques, such as ROS clearance and inflammation reduction under stressful conditions, show promise. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…17 Stressful conditions such as inflammation or elevated ROS levels cause chondrocyte anabolism to decrease, while catabolism increases, hastening the onset of OA. 18 As translational therapeutics, multifaceted techniques, such as ROS clearance and inflammation reduction under stressful conditions, show promise. 19,20 Herbal pharmaceutically active components, which have comprehensive therapeutic effects and few side effects on the human body, have particular effects and great development potential for lowering oxidative stress and treating KOA.…”
Section: Introductionmentioning
confidence: 99%